2018
DOI: 10.3389/fphar.2018.01197
|View full text |Cite
|
Sign up to set email alerts
|

XPA, XPC, and XPD Modulate Sensitivity in Gastric Cisplatin Resistance Cancer Cells

Abstract: Cisplatin is an election drug widely used in clinic for the treatment of advanced gastric cancer. However, the heterogeneity of the gastric tumors and its resistance to the drugs, make in some cases the response very low and the prognosis unpredictable. In this manuscript we aim to find the molecular processes involved in cisplatin-induced apoptosis in two gastric cancer cell lines with different sensitivity to the treatment: AGS and MKN45. The apoptosis induction is higher in MKN45 than in AGS cells in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Finally, the antiapoptotic Mcl1 expression analysis after 6 h of treatment shows that CDDP produces clear degradation as it is described in the literature after 48 h. 7 Compound 1 shows the same profile. No degradation is observed neither with 2 nor with 4 , but a surprisingly marked degradation is observed with 3 h treatment.…”
Section: Resultssupporting
confidence: 74%
“…Finally, the antiapoptotic Mcl1 expression analysis after 6 h of treatment shows that CDDP produces clear degradation as it is described in the literature after 48 h. 7 Compound 1 shows the same profile. No degradation is observed neither with 2 nor with 4 , but a surprisingly marked degradation is observed with 3 h treatment.…”
Section: Resultssupporting
confidence: 74%
“…ERCC2 encodes XPD, a protein associated with regulation of TFIIH-mediated transcription and DNA damage. XPD has effects on progression of a broad palette of tumor types when mutated or altered—increased or decreased—in expression, and variants in ERCC2 have been associated with altered drug response, especially platinum-based therapies ( Du et al., 2014 ; Fu et al., 2017 ; Tan et al., 2017 ; Pajuelo-Lozano et al., 2018 ; Liu et al., 2019 ). This may have contributed to the patient's failure to respond to earlier carboplatin-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of XPC to DNA is necessary for the recruitment of TFIIH, making it the rate-limiting step of GG-NER [ 58 ]. Studies have shown that enhanced expression of XPC increases resistance in many types of cancer [ 59 , 60 , 61 ]. Additionally, studies involving many different cancer cell lines have shown that the overexpression of XPC leads to cisplatin resistance ( Figure 2 ) while knockout of the gene enhances sensitivity.…”
Section: Dna Repair Pathwaysmentioning
confidence: 99%